EVOLUTION OF VIEWS ABOUT DEATH - Hakim Muhammadiyevich Jurayev (Western European Studies, 2024)
Life and death is a feature not only of world philosophy, but also of national philosophical thinking. In the second half of the 20th century, a system of objective knowledge in a certain sense was formed between philosophy and science to study the problem of death. From this point of view, it is currently included in the field of scientific research of social philosophy and is being researched by many specialists
Keywords: evolution; death; thought; knowledge